Students' Knowledge of Substance Abuse on Campus at Bab Zubair Colleges: Pengetahuan Mahasiswa tentang Penyalahgunaan Zat di Kampus di Perguruan Tinggi Bab Zubair - Khalaf, Firas Hadi; Mutashar, Mohammed Kadhim; Ali, Afnan Ahmed Abd (Universitas Muhammadiyah Sidoarjo, 2024)
Background: Substance abuse refers to consumption of psychoactive substances without experiencing any negative consequences He/she is doing it for social, experimental or recreational use. Objective: To assess demographical data of the students, to assess students’ knowledge level about addiction, to find out correlations among demographical data, and between knowledge. Methods: Study Design The research was conducted through descriptive design between the dates of November-April, 2024. The sample size of this descriptive study is 400, as planned; and the sample is 100 students only who fill in the data collection tools completely and who are volunteering in participating in the study , Only “100” of students were selected, a purposive sample type was initiated through a self-reported questionnaire , Organized random assignment of the sample was done in the four colleges separately, and at the same period. Each student is given a single paper of the instrument and he/she fill-in by him/her-self. Results: The results of the study show that there is a good knowledge among the students with total assessment was 2.47 (good). Highlights: Substance abuse involves psychoactive substance use without adverse consequences. Assess demographics, knowledge, and correlations regarding addiction among students. Students demonstrated good knowledge, scoring 2.47 (good) overall. Keywords: Students', substance abuse, Knowledge. Colleges, Assessment